2014
DOI: 10.1192/bjp.bp.113.134213
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole once-monthly for treatment of schizophrenia: double-blind, randomised, non-inferiority study

Abstract: Aripiprazole once-monthly 400 mg was non-inferior to oral aripiprazole, and the reduction in Kaplan-Meier estimated impending relapse rate at week 26 was statistically significant v. aripiprazole once-monthly 50 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
188
2
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(223 citation statements)
references
References 23 publications
16
188
2
15
Order By: Relevance
“…[15][16][17] The greater improvement observed in the PANSS total score associated with aripiprazole lauroxil 882 mg compared to aripiprazole lauroxil 441 mg in the subpopulation of more severe patients (mean [SD] PANSS score > 92 at baseline, 101.3 [6.0] for aripiprazole lauroxil 441 mg and 101.0 [6.4] for aripiprazole lauroxil 882 mg) suggests there may potentially be an additional benefit of the higher dose in patients experiencing more severe symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] The greater improvement observed in the PANSS total score associated with aripiprazole lauroxil 882 mg compared to aripiprazole lauroxil 441 mg in the subpopulation of more severe patients (mean [SD] PANSS score > 92 at baseline, 101.3 [6.0] for aripiprazole lauroxil 441 mg and 101.0 [6.4] for aripiprazole lauroxil 882 mg) suggests there may potentially be an additional benefit of the higher dose in patients experiencing more severe symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment discontinuation in the AOM group was notably lower than in the placebo group, and almost all patients stayed on their starting dose of 400 mg. Safety and tolerability were generally as expected on the basis of previous studies of AOM in stable patients with schizophrenia. 13,14 Collectively, the results suggest that AOM 400 mg is a viable treatment option for patients who experience an acute exacerbation of schizophrenia.Drug names: aripiprazole once-monthly (Abilify Maintena), clozapine (Clozaril, FazaClo, and others). …”
mentioning
confidence: 98%
“…Another explanation may relate to patient demographics; ~ 66% of patients in the current study were African American compared with ~ 20% in previous AOM studies, and mean weight gain at 12 weeks was numerically greater in African American than in white patients. 13,14 Increased risk for obesity and weight gain has been observed in African Americans with severe mental illness. …”
mentioning
confidence: 99%
“…Moreover, for the majority of patients, ALAI study [28] reported absence of any pain, redness, swelling and induration following the first and last injections of aripiprazole 400 mg monthly.…”
Section: Discussionmentioning
confidence: 95%